2001
DOI: 10.1007/s005200000190
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of vinorelbine phlebitis with cimetidine

Abstract: One hundred eighteen patients with various malignancies received a total of 847 vinorelbine (VNR) infusions, during 25 of which episodes of vinorelbine phlebitis occurred (1 in each of the 25 patients concerned). Venous irritation was graded with reference to the scale devised by Rittenberg et al. To prevent these 25 patients against further venous toxicity, we pretreated them with cimetidine 200 mg i.v. prior to VNR administration in subsequent cycles of chemotherapy. In most (19, or 76%) complete prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…On the basis of their results, we used the administration of 6 min infusion of vinorelbine as the control arm in this study. The use of defibrotide [12,13] as another anti-thrombotic drug, or cimetidine [14], which was reported to inhibit histamine actions in endothelial cells by vinorelbine [15], have been investigated in an attempt to reduce the incidence of local venous toxicity of vinorelbine. However, there have been no randomized controlled trials to verify the benefit of these methods, and thus a randomized controlled study is needed to draw definitive conclusions about their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of their results, we used the administration of 6 min infusion of vinorelbine as the control arm in this study. The use of defibrotide [12,13] as another anti-thrombotic drug, or cimetidine [14], which was reported to inhibit histamine actions in endothelial cells by vinorelbine [15], have been investigated in an attempt to reduce the incidence of local venous toxicity of vinorelbine. However, there have been no randomized controlled trials to verify the benefit of these methods, and thus a randomized controlled study is needed to draw definitive conclusions about their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest regimen‐specific toxicity seen was that of vinorelbine‐induced phlebitis with one‐fifth of the cycles producing symptomatic phlebitic responses although these were predominantly not severe (Table 2). Two recent publications have attempted to address this issue and have shown that both antihistamines and corticosteroids may be able to reduce the frequency and severity of vinorelbine‐induced phlebitis 22,23 . Such approaches should therefore be given consideration in future evaluations of this or similar salvage strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intravenous injection of vinorelbine often causes venous irritation such as erythema, injection site pain, and phlebitis. The incidence of venous irritation by vinorelbine is approximately 10-30% [4][5][6][7]. Venous irritation limits the continuation of chemotherapy and deteriorates the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%